Uji Aktivitas Inhibisi Isolat Kuersitrin dari Benalu Masisin Dendrophthoe pentandra (L.) Miq. terhadap Sel Leukemia L1210 - ERMIN KATRIN W.; RISMA MARISI TAMBUNAN; HENDIG WINARNO (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Parasitic plant [Dendrophthoe pentandra (L.) Miq.] on the masisin [Rhodomyrtus tomentosa (Aiton) Hassk.] was traditionally used for cancer treatment in Central Kalimantan. Maceration of dried Dendrophthoe pentandra using ethanol followed by ethyl acetate produced ethanol and ethyl acetate extracts which exhibit inhibitory activity against leukemia L1210 cells with IC50 of 17.3 and 20.9 µg/mL, respectively. Fractionation of ethyl acetate extract by column chromatography yielded 7 fractions (F1~F7). Inhibitory activity test on fractions F1~F7 against leukemia L1210 cells showed inhibitory activity with IC50 0f 19.9, 19.0, 20.7, 16.0, 13.7, 12.5, and 17.4 µg/mL, respectively. During evaporation of F5 by rotary evaporator, a yellowish precipitate was observed and identified as quercitrin (quercetin 3-O-rhamnoside). Inhibitory activity test on quercitrin against leukemia L1210 cell showed that the crystal has an IC50 of 14.7 µg/mL. Separation of F7 by semipreparative HPLC reverse phase column yielded isolate A and B which exhibited inhibitory activity on leukemia L1210 cells with IC50 of 15.0 and 14.4 µg/mL, respectively. Subsequent solvent partition of ethanol extract into ethyl acetate-water and separation of ethyl acetatesoluble portion by column chromatography produced 7 fractions (F8~F14). Further separation of F14 by column chromatography yielded quercitrin and isolate C which has not been identified yet.